Follow–up of females with atypical glandular cells on Pap smears: Sledenje žensk z atipičnimi žleznimi celicami v brisih materničnega vratu - Planinc, Ana; Repše Fokter, Alenka; Golouh, Rastko (Acta Medico-Biotechnica, 2021)
Purpose: Atypical glandular cells (AGC) are often associated with clinically significant lesions, but the interpretation of AGC and the associated lesions on Pap smears remains challenging, even for experienced cytopathologists. The frequency and histologic follow–up of AGC regardless of gland cell type were investigated.Methods: A retrospective review was conducted involving 199,265 cervicovaginal smears which were examined in the Department of Pathology and Cytology of Celje General Hospital between 1 January 2003 and 31 December 2008. We investigated the frequency of AGC on conventional Pap smears and evaluated the follow–up and correlation between cytology results and subsequent biopsy diagnoses over a 6–year period. The data were processed using the statistics program, SPSS. Statistical significance was set at a p
Keywords: cervical cancer screening program; Pap smears; atypical glandular cells; histologic follow– up